ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF DIFFERENT PLANTS EXTRACTS AGAINST STAPHYLOCOCCUS AUREUS ISOLATED FROM SOCCER PLAYER’S SHOES AND KNOWLEDGE AND APPLICATIONS ABOUT FOOT HYGIENE OF THE SOCCER PLAYERS - Okmen, Ahmet Sadan (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The microorganisms most commonly attacks the feet. Bacteria have an easier entry into the athlete’s epidermis. Staphylococcus aureus, commonly found on the skin or in the nose. The purpose of the study is to search the lack of knowledge about the antibacterial and antioxidant effects of different plants extracts and to search the knowledge about hygiene and hygiene of sports equipment of soccer players. Materials and Methods: The bacteria were isolated from soccer player’s shoes (n=28) from Balıkesir Spor soccer team after the competition. Additionally, ten plants were collected from Mugla, Hatay, and Hakkari in Turkey. In antibacterial activity studies, the plant materials were tested by disc diffusion assay. Furthermore, the different plants extracts were studied by ABTS decolorization assay. Results: The highest antibacterial activity was shown on S. aureus- BFT2 (22 mm) for Hypericum perforatum L. subsp. veranese (Schrant) H. Lindb. The different extracts possessed antibacterial activity, and showed MIC effect at 812.5 µg/mL. The antioxidant activities by ABTS assay were in the order of Arbutus andrachne (flower) > Arbutus andrachne (leaf) > Anthemis sp. (flower) > Crepis sancta L. (leaf) > Allium sphaerocephalon (root) > Plantango major (leaf) > Lavandula steochas (flower) > Anthemis sp. (flower) > Urtica dioica (leaf) > Lavandula steochas (leaf) > Anthemis sp. (leaf) > Hypericum perforatum L. subsp. veranese (Schrant) H. Lindb (flower) > Anthemis chia L. (leaf). Conclusion: Different plant extracts have antimicrobial, antioxidant and potential.